DO TEXTO À CANÇÃO: RELAÇÕES DIALÓGICAS ENTRE LITERATURA E MÚSICA EM MATO GROSSO DO SUL - ALAN SILUS DA CRUZ SILVA (2023)
This text aims to analyze the dialogical relations between literature and music in Mato Grosso do Sul through the study of two phonographic works whose bases are linked to poetic texts by authors from the state. This objective arises from the following question: what is the dialogic relationship established between music and regional literature from the way the word can be musicalized and through the poetic images that literature creates in/for music? To arrive at an attempt at an answer, we sought to analyze two works entitled Fiandeiras do Pantanal by Tetê Espíndola and Raquel Naveira and Crianceiras by Márcio de Camillo. As specific objectives we coined the following path: 1. Build a historical record about the Music of Mato Grosso do Sul, from its origins and its Popular Urban aspect; 2. Trace a historiographical panorama of Literature Sul-Mato-Grossense in order to situate the issue of written productions in the state as a basis for understanding the analyzed works; 3. Reflect on the dialogic relationships that the artistic discourse promotes from the intertwining of music with literature and, finally 4. Analyze two phonographic works whose bases are based on poets of Mato Grosso do Sul literature. As a methodological path, we sought, through a qualitative approach, to explore the existing bibliographies and virtual references for the construction of a historical-social path of literature and music produced in MS and, then, we developed a mapping of literary-musical works linked to artists of State. Finally, based on Dialogical Analysis of Discourse and Semiotics of Culture in dialogue with other studies and theories, we developed the analytical work of the two measured works. Finally, we consider that both in music and in literature, the analyzed works seek to demonstrate the marks of poetics present in the writers they propose to set to music, as well as through the arrangements and musical harmonies they denote how the musical expression focused on literary relations is constituted as mark of the cultural identity of MS. Keywords: Mato Grosso do Sul Literature; Sul-Mato-Grossense Music; Dialogical Discourse Analyses; Culture Semiotic; Litero-Musical Relations.